Tinjauan Literatur: The Role Of Work Engagement In Mediating The Effects Of Human Resource Planning And Compensation On The Sustainability Of Educational Institutions: An Integrative Literature Review - dissa melina; Aflidarneti; Gilang Dwi Nanda; M. Devi Triyanti Mukarto; M. Havidz Aima (Greenation Management and Business Review, 2026)
The sustainability of educational institutions amid technological disruption, regulatory changes, and increasingly intense competition depends substantially on their ability to manage human capital strategically. This study aims to analyze the effects of human resource planning and compensation on the sustainability of educational institutions, with work engagement serving as a mediating variable. The study employed an integrative literature review by identifying, evaluating, and synthesizing 16 relevant scholarly articles published within the last five years. The reviewed articles comprised 13 studies published in nationally accredited SINTA journals and three studies published in Scopus-indexed international journals. Literature searches were conducted through Garuda, Google Scholar, and Scopus using keywords related to human resource planning, compensation, work engagement, and institutional sustainability. The selected literature was analyzed thematically to identify patterns and relationships among the principal variables. The findings indicate that strategic human resource planning contributes to institutional sustainability through accurate workload allocation, competency-based recruitment, career development, succession planning, and improved operational efficiency. Fair and competitive financial and non-financial compensation strengthens employee retention, motivation, and organizational commitment. However, the effects of these managerial practices on institutional sustainability are not always direct. Work engagement, as reflected in vigor, dedication, and absorption, functions as a central psychological mechanism that transforms supportive human resource policies into productive behavior, innovation, loyalty, and extra-role performance. This review concludes that work engagement plays a crucial mediating role in the relationship between human resource planning, compensation, and the sustainability of educational institutions. Educational leaders should therefore adopt an engagement-centered human capital management approach that integrates transparent career planning, equitable compensation, employee well-being, and participatory communication.